2019
DOI: 10.1093/milmed/usy329
|View full text |Cite
|
Sign up to set email alerts
|

I’m Wearing My Hearing Protection – Am I Still At Risk for Hearing Loss? Lurking Ototoxins in the Military Environment

Abstract: Objective Information is summarized from the overall body of published literature regarding ototoxic chemicals encountered outside of clinical exposures, largely in occupational settings. While summarizing the most common non-pharmaceutical ototoxins, this review provides clinically relevant information and recommendations such that hearing health professionals may adopt a more comprehensive and appropriate diagnostic case history, test battery, documentation scheme, and education delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Another approach involves conducting a risk assessment for the combination of noise and ototoxic chemical exposure. European countries in the European Noise Directive indicated that the interactions of noise with other risks (ototoxicants) must be given special consideration by the employer by conducting a risk assessment (24) The statement is in accordance with previous studies that suggested even though noise levels are below the legal limit, workers are still encouraged to wear hearing protection equipment while exposed to noise and ototoxicants concurrently (16)(17)23). Similarly, the Spanish transposition of the Noise Directive has clearly stated that ototoxicity could be prevented by controlling exposure using a suitable PPE while being exposed to the ototoxicants (32).…”
Section: Exposure-based Approachsupporting
confidence: 66%
See 4 more Smart Citations
“…Another approach involves conducting a risk assessment for the combination of noise and ototoxic chemical exposure. European countries in the European Noise Directive indicated that the interactions of noise with other risks (ototoxicants) must be given special consideration by the employer by conducting a risk assessment (24) The statement is in accordance with previous studies that suggested even though noise levels are below the legal limit, workers are still encouraged to wear hearing protection equipment while exposed to noise and ototoxicants concurrently (16)(17)23). Similarly, the Spanish transposition of the Noise Directive has clearly stated that ototoxicity could be prevented by controlling exposure using a suitable PPE while being exposed to the ototoxicants (32).…”
Section: Exposure-based Approachsupporting
confidence: 66%
“…There were 16 selected full text items consisting of eight (n=8) published articles (16)(17)(18)(19)(20)(21)(22)(23) and eight (n=8)…”
Section: Data Typementioning
confidence: 99%
See 3 more Smart Citations